Bimetallic Group 4 complexes as olefin polymerisation catalysts - Collins, RA (2016)
This Thesis describes the synthesis and characterisation of half-sandwich bimetallic complexes supported by κ1-amidinate ligands with different bridging moieties. Chapter 1 introduces homogeneous polyolefin catalysis with a focus on Group 4 metals. The mechanism, catalyst development and the activation chemistry of metallocene and post-metallocene catalysts are discussed. The beneficial properties generated by bimetallic catalysts through cooperative interactions are introduced. Chapter 2 describes the synthesis, structures and copolymerisation capabilities of cyclopentadienyl-amidinate phenylene bridged bimetallic titanium complexes. A series of monometallic cyclopentadienyl-amidinate dimethyl and dichloride titanium complexes are presented for comparison. A detailed description of their activation to form well-defined cationic species is presented. Chapter 3 describes the synthesis, structures and copolymerisation capabilities of cyclopentadienyl-amidinate titanium bimetallic complexes with conformationally constrained and ferrocenyl covalent tethers. Alongside the ferrocenyl complexes introduced in Chapter one, an electrochemical analysis of all ferrocene based complexes will be discussed. Chapter 4 details two different binuclear cocatalysts and their performances in a high temperature EPDM copolymerisation study. The form of the catalytic species is investigated through abstraction reactions with monometallic and bimetallic complexes previously introduced. Chapter 5 describes the synthesis of a bimetallic zirconium complex and attempted synthesis of a Group 4 heterobimetallic complex. A parallel polymerisation reactor (PPR) experiment on in situ generated precatalysts is discussed, which is supported by synthetic and polymerisation experiments. Chapter 6 presents full experimental procedures and characterising data for the new complexes reported in this Thesis.